We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
96
1
avatar

If a, b, c and d are positive real numbers such that log_a  b= 8/9, log_b  c= -(3/4), log_c d = 2, 

 

find the value of log_d (abc)

 Feb 22, 2019
 #1
avatar+22574 
+3

If a, b, c and d are positive real numbers such that
log_a  b= 8/9,
log_b  c= -(3/4),
log_c d = 2,
find the value of log_d (abc)

 

\(\begin{array}{|rclcl|} \hline \log_a(b) &=& \dfrac{\log_d(b)}{\log_d(a)} &=& \dfrac{\log_b(b)}{\log_b(a)} \\\\ & & \dfrac{\log_d(b)}{\log_d(a)} &=& \dfrac{\log_b(b)}{\log_b(a)} \quad | \quad \log_b(b) = 1 \\\\ & & \dfrac{\log_d(b)}{\log_d(a)} &=& \dfrac{1}{\log_b(a)} \quad | \quad \log_a(b)\log_b(a)=1 \\\\ & & \dfrac{\log_d(b)}{\log_d(a)} &=& \log_a(b) \\\\ & & \dfrac{\log_d(a)} {\log_d(b)}&=& \dfrac{1}{\log_a(b)} \\\\ & & \mathbf{\log_d(a)} & \mathbf{=} & \mathbf{ \dfrac{\log_d(b)}{\log_a(b)} } \qquad (1) \\ \hline \log_b(c) &=& \dfrac{\log_d(c)}{\log_d(b)} &=& \dfrac{\log_c(c)}{\log_c(b)} \\\\ & & \dfrac{\log_d(c)}{\log_d(b)} &=& \dfrac{\log_c(c)}{\log_c(b)} \quad | \quad \log_c(c) = 1 \\\\ & & \dfrac{\log_d(c)}{\log_d(b)} &=& \dfrac{1}{\log_c(b)} \quad | \quad \log_b(c)\log_c(b)=1 \\\\ & & \dfrac{\log_d(c)}{\log_d(b)} &=& \log_b(c) \\\\ & & \dfrac{\log_d(b)}{\log_d(c)} &=& \dfrac{1}{\log_b(c)} \\\\ & & \mathbf{\log_d(b)} &\mathbf{=}& \mathbf{\dfrac{\log_d(c)}{\log_b(c)}} \qquad (2) \\ \hline && \log_c(d) &=& \dfrac{\log_d(d)}{\log_d(c)} \quad | \quad \log_d(d) = 1 \\\\ && \log_c(d) &=& \dfrac{1}{\log_d(c)} \\\\ & & \mathbf{\log_d(c)} &\mathbf{=}& \mathbf{\dfrac{1}{\log_c(d)}} \qquad (3) \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \log_d(abc) &=& \log_d(a)+\log_d(b)+\log_d(c) \quad | \quad \mathbf{\log_d(a)=\dfrac{\log_d(b)}{\log_a(b)} } \qquad (1) \\ &=& \dfrac{\log_d(b)}{\log_a(b)}+\log_d(b)+\log_d(c) \\ &=& \log_d(b) \left( \dfrac{1}{\log_a(b)}+1 \right) +\log_d(c) \quad | \quad \mathbf{\log_d(b)=\dfrac{\log_d(c)}{\log_b(c)}} \qquad (2) \\ &=& \dfrac{\log_d(c)}{\log_b(c)} \left( \dfrac{1}{\log_a(b)}+1 \right) +\log_d(c) \\ &=&\log_d(c)\left( \dfrac{1}{\log_b(c)} \left( \dfrac{1}{\log_a(b)}+1 \right) + 1 \right) \quad | \quad \mathbf{\log_d(c)=\dfrac{1}{\log_c(d)}} \qquad (3) \\ \mathbf{\log_d(abc)} & \mathbf{=} & \mathbf{\dfrac{1}{\log_c(d)}\left( \dfrac{1}{\log_b(c)} \left( \dfrac{1}{\log_a(b)}+1 \right) + 1 \right)} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \mathbf{\log_d(abc)} & \mathbf{=} & \mathbf{\dfrac{1}{\log_c(d)}\left( \dfrac{1}{\log_b(c)} \left( \dfrac{1}{\log_a(b)}+1 \right) + 1 \right)} \\\\ & = & \dfrac{1}{2}\left( \dfrac{1}{ -\dfrac{3}{4} } \left( \dfrac{1}{\dfrac{8}{9}}+1 \right) + 1 \right) \\\\ & = & \dfrac{1}{2}\left( \dfrac{-4}{3} \Big( \dfrac{1}{8}+1 \Big) + 1 \right) \\\\ & = & \dfrac{1}{2}\left( \dfrac{-4}{3} \left( \dfrac{17}{8} \right) + 1 \right) \\\\ & = & \dfrac{1}{2}\left( \dfrac{-17}{6} + 1 \right) \\\\ & = & \dfrac{1}{2}\left( \dfrac{-11}{6} \right) \\\\ & \mathbf{=} & -\mathbf{\dfrac{11}{12}} \\ \hline \end{array}\)

 

laugh

 Feb 22, 2019
edited by heureka  Feb 22, 2019

11 Online Users